2012
DOI: 10.1111/jvh.12023
|View full text |Cite
|
Sign up to set email alerts
|

In vivo infectivity of liver extracts after resolution of hepadnaviral infection following therapy associating DNA vaccine and cytokine genes

Abstract: SUMMARY. DNA-based vaccination appears of promise for chronic hepatitis B immunotherapy, although there is an urgent need to increase its efficacy. In this preclinical study, we evaluated the therapeutic benefit of cytokine (IL-2, IFN-c) genes co-delivery with DNA vaccine targeting hepadnaviral proteins in the chronic duck hepatitis B virus (DHBV) infection model. Then, we investigated the persistence of replication-competent virus in the livers of apparently resolved animals. DHBV carriers received four injec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 43 publications
0
7
0
Order By: Relevance
“…Even though the initial infection might have been in PHH, the changing phenotype of cells during culture makes interpretation of results difficult. In vivo however, HBV can be transmitted by low pathogen numbers and in the absence of immunomodulation 12 , 13 . This raises the question as to whether a more natural host cell environment including a physiological liver architecture resembling liver sinusoids would impact the susceptibility to infection of PHH with HBV.…”
Section: Introductionmentioning
confidence: 99%
“…Even though the initial infection might have been in PHH, the changing phenotype of cells during culture makes interpretation of results difficult. In vivo however, HBV can be transmitted by low pathogen numbers and in the absence of immunomodulation 12 , 13 . This raises the question as to whether a more natural host cell environment including a physiological liver architecture resembling liver sinusoids would impact the susceptibility to infection of PHH with HBV.…”
Section: Introductionmentioning
confidence: 99%
“…Following the discovery of DNA vaccine technology approximately 20 years ago, significant progress has been made in optimizing their function (Wu et al 2011;Gao et al 2013;Obeng-Adjei et al 2013;Saade et al 2013;Endmann et al 2014;Yoon et al 2015). Post-translational modification of newly synthesized antigens has proven important in determining the level and type of immune response.…”
Section: Discussionmentioning
confidence: 99%
“…They can be produced by stimulation with PRR agonist, and TLR8 agonist has been shown to be very potent in this respect in the liver 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 63 64 65 17 (Jo et al, 2014). Recombinant forms of these cytokines have not yet been widely used, but several trials performed in animal model or in human, and aiming at investigating DNA vaccination as therapeutic approach have used co-injection of vectors encoding these chemokines, and shown that they indeed improved immune responses (Brass et al, 2015;Chow et al, 1998;Saade et al, 2013;Yang et al, 2012).…”
Section: Chemokines As Adjuvant?mentioning
confidence: 96%